A baseline study on the distribution characteristics and health risk assessment of cadmium in edible tissues of the swimming crabs (Portunus trituberculatus) from Shanghai, China. (December 2022) - Wu, Di; Shi, Yongfu; Wang, Mengyuan; Ran, Maoxia; Wang, Yuan; Tian, Liangliang; Ye, Hongli; Han, Feng
Abstract: This study analyzed the cadmium accumulation differences in edible tissues of the swimming crabs ( Portunus trituberculatus ) from Shanghai markets, which were mostly caught in the East China Sea, and the human health risk of cadmium from crabs consumption was evaluated. A total of 78 swimming crabs were collected, and the white meat and brown meat were separated for the cadmium analysis by Inductively coupled plasma mass spectrometry. The results revealed that there was difference in cadmium content in brown meat (1.260–16.303 mg/kg) and white meat (0.005–0.542 mg/kg). Furthermore, pollution index (Pi) results showed that only the claw muscle was at low contamination levels, while other edible tissues had varying degrees of contamination. Based on the health risk assessment by estimated daily intake (EDI), target hazard quotient (THQ) and target cancer risk (TCR), the consumption of the swimming crabs in Shanghai is considered safe, however, the accumulation of cadmium in the brown meat of swimming crabs deserves further attention and evaluation. Graphical abstract: Unlabelled Image Highlights: Cadmium concentrations were revealed among edible tissues of swimming crabs. Hepatopancreas and gonads are the primary accumulation sites of cadmium. Hazard quotients for consuming brown meat is about 5 times higher than white meat. Consumption of swimming crabs is unlikely to cause human health risk, for now.